ANALISIS FAKTOR EKOLOGI TERHADAP ADMINISTRASI NEGARA DALAM TRANSFORMASI ADMINISTRASI MODERN - Fakhsiannor Fakhsiannor (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2016)
Administration as a science has a general nature and universal in the sense of having the same elements, wherever and whenever science of administration is set. But in fact, its found a wide variety and indication of administration that contained in some groups of society from one nation or among various nations. Growth in developing countries ecology administration since 1950, where the problem is the environment which has a variety of aspects that need estabilishing which aspects are relevant for system of state administration or the nationalities. Even in a system of state administration was still found subsystem administration of a group of society who came from thr territory of a certain country, seemingly there was a relationship of influence between administration of a part of the terriory with the surrounding community, both the physical environment and community circles viewed from the science of biology, its an ecology that studies the relationship of reciprocal influence between the natural surroundings with a living organism.